Agency and Structure in Socially Engaged Buddhist Economics - Magnuson, Joel Cameron (Canadian Journal of Buddhist Studies, 2023)
The dialectical interplay of agency and structure is a key part of Socially Engaged Buddhist Economics. It has been present in economic discourse over the last several decades, particularly in heterodox approaches that view economics from historical and sociological perspectives. In this article I join the discourse with a new approach by integrating aspects of pragmatism, institutional economics, process metaphysics, and Buddhism. The basic ideas underpinning this integration are (a) that both agent and structure are emergent phenomena and (b) that agency can be seen in a more comprehensive way through the lens of George H. Mead’s conception of the "social self." Mead’s social self is split into a bipolar model of the subjective I and the objective me. Together these ideas are combined into a single framework of agent, structure, I, and me (ASIM) with implications for ethics as well as Buddhist economics.,